2012
DOI: 10.1159/000336844
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Facets of Dermcidin in Cell Survival and Host Defense

Abstract: Eccrine sweat glands, which are distributed over the whole bodies of primates and humans, have long been regarded mainly to have a function in thermoregulation. However, the discovery of dermcidin-derived antimicrobial peptides in eccrine sweat demonstrated that sweat actively participates in the constitutive innate immune defense of human skin against infection. In the meantime, a number of studies proved the importance of dermcidin in skin host defense. Several reports also state that peptides processed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 152 publications
2
74
1
5
Order By: Relevance
“…Indeed, applying our classification methods to AJCC stage I–II patients revealed that the stage II patients with DCD levels <2.98 μg/ml are more likely to develop metastasis during follow‐up (80% correctly classified instances). Elevated DCD levels have also been found in the serum of breast cancer patients collected at the time of diagnosis,44 although DCD expression in these tumor cells is associated with advanced clinical stage and poor disease prognosis 45. By contrast, in our group of melanoma patients, lower level of DCD was a significant factor that predicted a metastatic outcome in AJCC stage II patients.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, applying our classification methods to AJCC stage I–II patients revealed that the stage II patients with DCD levels <2.98 μg/ml are more likely to develop metastasis during follow‐up (80% correctly classified instances). Elevated DCD levels have also been found in the serum of breast cancer patients collected at the time of diagnosis,44 although DCD expression in these tumor cells is associated with advanced clinical stage and poor disease prognosis 45. By contrast, in our group of melanoma patients, lower level of DCD was a significant factor that predicted a metastatic outcome in AJCC stage II patients.…”
Section: Discussionmentioning
confidence: 53%
“…There is a growing interest in dermcidin since its discovery in 2001 (23). The role of DCD in cancer proliferation is of particular interest as the DCD-derived peptide Y-P30 has been shown to provide a cancer-associated function in the prostate (26).…”
Section: Resultsmentioning
confidence: 99%
“…In each analysis, we also found peptide fragments that corresponded to the 30 aa proteolysisinducing factor (PIF) core, 13 aa propeptide, and 47 aa DCD-1 peptide region of the poorly characterized dermcidin protein (DCD) (Fig. 4A) (23). LC-MS/MS analyses also identified a 12-kDa band as DCD itself (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 89%
“…Esta proteína foi primeiramente identificada em glândulas sudoríparas (Schittek;Hipfel et al, 2001), contribuindo para a primeira linha de defesa da pele por constituir uma barreira constante que recobre o epitélio (Schittek;Paulmann et al, 2008;Wiesner e Vilcinskas, 2010). Contudo, posteriormente, essa proteína foi encontrada também em células neuronais e leucócitos de sangue periférico (Schittek, 2012).…”
Section: Discussionunclassified
“…Contudo, posteriormente, essa proteína foi encontrada também em células neuronais e leucócitos de sangue periférico (Schittek, 2012).…”
Section: Discussionunclassified